Applying the multistate capture–recapture robust design to characterize metapopulation structure. Issue 11 (8th May 2017) - Chabanne, Delphine B. H.; Pollock, Kenneth H.; Finn, Hugh; Bejder, Lars
Summary: Population structure must be considered when developing mark–recapture (MR) study designs as the sampling of individuals from multiple populations (or subpopulations) may increase heterogeneity in individual capture probability. Conversely, the use of an appropriate MR study design which accommodates heterogeneity associated with capture occasion varying covariates due to animals moving between 'states' (i.e. geographic sites) can provide insight into how animals are distributed in a particular environment and the status and connectivity of subpopulations. The multistate closed robust design (MSCRD) was chosen to investigate: (i) the demographic parameters of Indo‐Pacific bottlenose dolphin ( Tursiops aduncus ) subpopulations in coastal and estuarine waters of Perth, Western Australia; and (ii) how they are related to each other in a metapopulation. Using 4 years of year‐round photo‐identification surveys across three geographic sites, we accounted for heterogeneity of capture probability based on how individuals distributed themselves across geographic sites and characterized the status of subpopulations based on their abundance, survival and interconnection. MSCRD models highlighted high heterogeneity in capture probabilities and demographic parameters between sites. High capture probabilities, high survival and constant abundances described a subpopulation with high fidelity in an estuary. In contrast, low captures, permanent and temporary emigration and fluctuating abundances suggested transient use and low fidelity in an open coastline site. Estimates of transition probabilities also varied between sites, with estuarine dolphins visiting sheltered coastal embayments more regularly than coastal dolphins visited the estuary, highlighting some dynamics within the metapopulation. Synthesis and applications . To date, bottlenose dolphin studies using mark–recapture approach have focussed on investigating single subpopulations. Here, in a heterogeneous coastal–estuarine environment, we demonstrated that spatially structured bottlenose dolphin subpopulations contained distinct suites of individuals and differed in size, demographics and connectivity. Such insights into the dynamics of a metapopulation can assist in local‐scale species conservation. The MSCRD approach is applicable to species/populations consisting of recognizable individuals and is particularly useful for characterizing wildlife subpopulations that vary in their vulnerability to human activities, climate change or invasive species.